EFEKTIVITAS MODEL TEAM-BASED PROJECT DENGAN MODEL SNOWBALL THROWING TERHADAP PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI KELAS VIII SMPN 1 CIBALONG KABUPATEN GARUT - Erni Fitriani; Lina Siti Nurwahidah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
One of the essential components of learning the Indonesian language that junior high school students must master is the ability to write report texts based on observation results. However, many students face difficulties in composing reports that follow proper rules and structure. Therefore, to enhance students’ writing skills, an effective learning model must be implemented. The purpose of this study is to compare the effectiveness of the Team-Based Project model and the Snowball Throwing model in improving the report-writing abilities of eighth-grade students at SMPN 1 Cibalong, Garut Regency, based on observation results. The method used is quasi-experimental, with a pretest-posttest control group design. To compare the posttest results of the two groups, non-parametric tests such as the Shapiro-Wilk normality test, Levene's homogeneity test, t-test, and Mann-Whitney test were used to analyze the data. The results show that both learning models significantly improved students’ writing abilities, as indicated by normalized gain scores falling within the moderate to high category. However, based on the higher average normalized gain score, the Team-Based Project model demonstrated a greater improvement compared to the Snowball Throwing model.